2021
DOI: 10.3389/fpls.2021.700975
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chloroplast Protein RNA Processing 8 Is Required for the Expression of Chloroplast Genes and Chloroplast Development in Arabidopsis thaliana

Abstract: Chloroplast development involves the coordinated expression of both plastids- and nuclear-encoded genes in higher plants. However, the underlying mechanism still remains largely unknown. In this study, we isolated and characterized an Arabidopsis mutant with an albino lethality phenotype named RNA processing 8 (rp8). Genetic complementation analysis demonstrated that the gene AT4G37920 (RP8) was responsible for the mutated phenotype. The RP8 gene was strongly expressed in photosynthetic tissues at both transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
3
2
0
Order By: Relevance
“…Our analysis of subcellular location confirmed that YCO is located within the chloroplast (Fig. 3), aligning with the previous studies (Chen et al 2022;Kong et al 2021). Hence, YCO protein was required for thylakoid membrane formation and chloroplast development.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our analysis of subcellular location confirmed that YCO is located within the chloroplast (Fig. 3), aligning with the previous studies (Chen et al 2022;Kong et al 2021). Hence, YCO protein was required for thylakoid membrane formation and chloroplast development.…”
Section: Discussionsupporting
confidence: 92%
“…3 C). Therefore, it appears this protein is localized to the chloroplast in Arabidopsis, which is consistent with previous reports (Chen et al 2022;Kong et al 2021).…”
Section: The Atyco Gene Displays Widespread Expressionsupporting
confidence: 93%
See 3 more Smart Citations